History of modern Europe - Gooch, G. P. (Henry Holt and Company, 1923)
It is impossible within the limits of a single volume to do justics to a period crowded with events, fermenting with new ideas, and enriched by the triumphs of invention and discovery. The theme of this book is the relations of the Great Powers of Europe to one another. It is history of Europe, not a history of the world.